1977
DOI: 10.1080/00021369.1977.10862452
|View full text |Cite
|
Sign up to set email alerts
|

Studies on New Antimetabolite N-1409

Abstract: New antimetabolite N-1409, an antagonist of L-threonine was isolated from the fermentation broth of Streptomyces. Taxonomical study on the producing strain made it a new species and named Streptomyces plumheus n. sp. Sakai et Park after its leaden color of matured aerial mycelium.N-1409 substance was isolated as colorless needles, mp 218~220°C. Its molecular formula C12H 21N.08P·3/2 H 20 was determined by elementary analysis and alkali titration. On acid hydrolysis, L-alanine, L-aspartic acid and a new phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Accordingly, all compounds described during this time period have known bioactivities. Fosfomycin (phosphonomycin) [19,8], bialaphos (SF-1293, phosphinothricin tripeptide, PTT) [1,41], phosalacine [45,46], trialaphos [28], dehydrophos (A53868) [24], FR-900098 [43], fosmidomycin [44], the plumbemycins [47,49,48], SF-2312 [60], and fosfonochlorin [58] were originally isolated by assaying inhibition of bacterial growth. Inhibition of fungal growth was used in isolation of the fosfazinomycins [18,42] and the rhizocticins [51], while inhibition of angiotensin converting enzyme (ACE) activity was used in discovery of I5B2 [29] and K-26 [65], and prevention of seed germination in the discovery of phosphonothrixin [33,57].…”
Section: The Discovery Of Phosphonate Natural Product Antibioticsmentioning
confidence: 99%
“…Accordingly, all compounds described during this time period have known bioactivities. Fosfomycin (phosphonomycin) [19,8], bialaphos (SF-1293, phosphinothricin tripeptide, PTT) [1,41], phosalacine [45,46], trialaphos [28], dehydrophos (A53868) [24], FR-900098 [43], fosmidomycin [44], the plumbemycins [47,49,48], SF-2312 [60], and fosfonochlorin [58] were originally isolated by assaying inhibition of bacterial growth. Inhibition of fungal growth was used in isolation of the fosfazinomycins [18,42] and the rhizocticins [51], while inhibition of angiotensin converting enzyme (ACE) activity was used in discovery of I5B2 [29] and K-26 [65], and prevention of seed germination in the discovery of phosphonothrixin [33,57].…”
Section: The Discovery Of Phosphonate Natural Product Antibioticsmentioning
confidence: 99%
“…The aqueous layer was subjected to paper chromatography (p.c.) using solvent system (1). The only detectable amino acid spot from hydrazinolyzate of PA and PB was one due to APPA at RfO.17.…”
Section: Dss Omentioning
confidence: 98%
“…It has been demonstrated that plumbemycins also enter Escherichia coli K-12 via the oligopeptide transport system (Diddens et al, 1979). As in the case of rhizocticins, l -threonine reverses the growth inhibition by plumbemycins in a concentration-dependent manner (Park et al, 1977b). Therefore, similarly to rhizocticins, plumbemycins must be cleaved by peptidases of the target cell to release the active substance, APPA.…”
Section: Introductionmentioning
confidence: 97%
“…They are di- and tripeptide antibiotics consisting of a variable amino acid at the N-terminus followed by arginine and the non-proteinogenic amino acid ( Z )- l -2-amino-5-phosphono-3-pentenoic acid (APPA, Figure 1 A). Interestingly, APPA is also the C-terminal amino acid of the tripeptide antibiotics plumbemycin A and B produced by Streptomyces plumbeus (Figure 1 B) (Park et al, 1977a; Park et al, 1977b). …”
Section: Introductionmentioning
confidence: 99%